PEMBERIAN EDUKASI PEMBIASAAN MENGGOSOK GIGI 21 HARI PADA SISWA SD AL AZHAR PROGRAM BULAN KESEHATAN GIGI NASIONAL 2024 “SCHOOL HEALTH PROGRAM”: PROVISION OF EDUCATION ON THE HABIT OF BRUSHING TEETH FOR 21 DAYS TO AL AZHAR ELEMENTARY SCHOOL STUDENTS NATIONAL DENTAL HEALTH MONTH PROGRAM 2024 “SCHOOL HEALTH PROGRAM” - Icha Artyas Annariswati; Dyah Ayu Retnowulan; Endah Wahjuningsih; Cane Lukisari; Arya Brahmanta; Emy Khoironi; Hansen Kurniawan; Eddy Hermanto; Hery Supriyadi; Meinar Nur Ashrin; MeraldaRsoyy; Widyastuti; Novendy Yoyada; Budi Santoso (Jurnal Pengabdian Masyarakat Pesisir, 2025)
Oral health in Indonesia is still a health problem that needs attention. Based on the 2018 Basic Health Research (Riskesdas), it is reported that the prevalence of oral and dental problems in Indonesia is still very high. The above can be caused by the lack of knowledge and lack of awareness of the Indonesian population towards dental hygiene, to overcome oral health problems in Indonesia Training of Trainers for teachers and parents for 21-day morning and night brushing activities teaches children and adults about the benefits of good oral hygiene and shows them how to brush their teeth twice a day with fluoride toothpaste to realize caries-free Indonesia in 2030. This activity is held online through the zoom application. The target participants were elementary school and inclusive school students aged 7-12 years, 10 parents and 10 teachers at SD Al Azhar Kelapa Gading Surabaya. The mechanism of the activity is “Training of Trainer” (TOT) for students and parents, showing that Training of Trainer activities on teachers and parents of SD Al Azhar Kelapa Gading Surabaya students can increase their knowledge and awareness on oral health.